ANALISIS KINERJA KEUANGAN PERUSAHAAN SUB-SEKTOR HOTEL, RESTORAN DAN PARIWISATA SEBELUM DAN SAAT PANDEMI COVID-19 - Oktavia, Erika; Suhendah, Rousilita (Jurnal Paradigma Akuntansi, 2025)
This research aims to examine differences in the financial performance of companies in the hotel, restaurant and tourism sub-sector before and during the COVID-19 pandemic which were listed on the Indonesia Stock Exchange for the period 2019 and 2020. The sample in this study was selected based on purposive sampling with certain criteria, resulting in 33 companies operating in the hotel, restaurant and tourism sub-sectors. This research also uses secondary data in the form of financial reports obtained from the sites www.Idx.co.id and www.britama.com. The data in this research was processed using the SPSS and Microsoft Excel programs. The results of this research show that there are significant differences in profitability, leverage and activity before and during the COVID-19 pandemic. Meanwhile, there was no significant difference in liquidity before and during the COVID-19 pandemic.